Role of Altruism and Amnesia on Players’ Health in China - Ding, Yongjiang; Zhifeng Tang , (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
Health is a core issue for any age sector especially in the sports industry where players are to perform. Hence, the core objective of the current study is to determine the relationship between psychological factors and players’ heath in China. Players’ health is explored to identify risks that are likely preventable or reversible to develop approaches to make players’ health better. To gain the results of the current study quantitative research technique was adopted. Hence a survey from 750 respondents of this study, was conducted to collect primary data. Then this primary data was analyzed with the help of a statistical software; Partial Least Square (PLS) to obtain the end results. The increased value of altruism in the players, increases their confidence. The players because of more values for their altruistic nature, are more confident and enjoy better health. While the players with the increased value of Amnesia easily lose their confidence and health. The current study provides robust knowledge to the players and athletes to understand the role of altruism and amnesia on their health and confidence.